Spatial Diversity of the Biotechnological Industry’s Development - Dorocki, Sławomir; Borowiec, Monika; Boguś, Marta (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
Today’s biotechnology is widely regarded as one of the most important sectors of infor- mation technology, a new wave of a knowledge-based economy. It is characterized by innovation and a very fast pace of development, which is connected with the involvement of highly qualified specia- lists, research centres, varied sources of information, investments, as well as interconnections to gu- arantee the flow of information. Biotechnology has got a potential wide range of applications, such as the food industry, production of genetically modified organisms, pharmaceutics, healthcare, detergents and bioremediation, forestry and agriculture. The aim of the article is to show the diversity in the development and structure of biotechnology in the world as well as in Poland. There is a huge variety in the world when it comes to the structure and space where the biotech development occurs. According to the collected data, even though the dynamic expansion of biotechnology takes place in new centers of development in Lithuania, Spain, Turkey and Slovakia, there is an obvious predominant role of highly developed countries. In Poland, biotechnology is mainly based on the potential of universities’ scientific centers and metropolitan centers. Furthermore, biotech development is determined by several factors. The distance from scientific cen- ters, location of universities, financial sources and international cooperation must be taken into consi- deration. Policy of a country is also one of the major determinants.